A population description of CULAs using combined documentation of compound phenotypes according to the Oberg-Manske-Tonkin classification - Feikje Julia ten Cate; Margriet Harmke Maria van Doesburg (JPRAS Open)
SUMMARY: Background/Purpose: Congenital upper limb anomalies (CULAs) exhibit a wide range of manifestations. For this reason, the Oberg-Manske-Tonkin (OMT) classification was introduced to achieve etiologically correct and universal classification. Combined use of codes has been advocated to prevent the loss of important phenotypic information in compound phenotypes. Therefore, the aim of our study was to present a description of our population over the last 10 years, using the most recent (2020) version of the OMT and combined documentation when necessary. Methods: All patients who visited our tertiary referral hospital between 2010 and 2020 were analyzed retrospectively and classified using the OMT. Combined registration was allowed in compound phenotypes and combinations were analyzed. Results: Overall, 797 patients were included in our registry. Most anomalies were classified in the malformations group and 9.5% required combined documentation; 13.5% of the possible combinations were observed in opposite extremities. Syndactyly, polydactyly (radial and ulnar), and camptodactyly were the most common diagnoses. The most frequently observed recurring combinations were brachydactyly and clinodactyly, ulnar longitudinal deficiency and simple syndactyly, and simple syndactyly and clinodactyly. Conclusions: Approximately one-tenth of our population required combined documentation. When using compound documentation, we recommend providing information regarding the presence or absence of a combination in the same extremity. Failing to do so could lead to loss of equally important phenotypic information as disregarding combinations would. Epidemiologic registries such as ours, allow outcome comparison and provide information for research on underlying etiologies. Additionally, our research focused on the analysis of combinations of codes.Level of evidence: 3